Comparison of the growth of oil sardine Sardinellalongiceps Val., off Vishakhapatnam and Malabarcoasts - Ganga, U; Pillai, N G K (Indian Journal of Fisheries, 2011)
The growth of oil sardine, Sardinella longiceps off Visakhapatnam and Malabarcoast was compared. Hydrological and productivity regimes are found to influencethe growth pattern of oil sardine. Growth pattern of oil sardine exhibitedseasonality, which was more pronounced along the Malabar coast than offVisakhapatnam.